Sequence and series (8) reborn

Algebra Level pending

Let { a n } \{a_n\} be a sequence satisfying

{ a 0 = 3 ( 3 a n ) ( 6 + a n 1 ) = 18 for n 1 \begin{cases} \begin{aligned} a_0 & = 3 \\ (3-a_n)(6+a_{n-1}) & = 18 & \text{for }n \ge 1 \end{aligned} \end{cases}

If 1 a 0 + 1 a 1 + 1 a 2 + 1 a 100 = 2 α β γ \dfrac 1{a_0} + \dfrac 1{a_1} + \dfrac 1{a_2} \cdots + \dfrac1a_{100} = \dfrac{2^\alpha - \beta}{\gamma} , find α + β + γ \alpha + \beta + \gamma .


The answer is 208.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Apr 30, 2020

Given that ( 3 a n ) ( 6 + a n 1 ) = 18 (3-a_n)(6+a_{n-1}) = 18 , then

a n 1 = 3 18 6 + a n 1 = 3 a n 1 6 + a n 1 1 a n = 2 a n 1 + 1 3 Let b k = 1 a k b n = 2 b n 1 + 1 3 b 0 = 1 a 0 = 1 3 = 2 1 1 3 b 1 = 2 3 + 1 3 = 1 = 2 2 1 3 b 2 = 2 + 1 3 = 7 3 = 2 3 1 3 b n = 2 n + 1 1 3 See proof below. \begin{aligned} a_{n-1} & = 3-\frac {18}{6+a_{n-1}} = \frac {3a_{n-1}}{6+a_{n-1}} \\ \frac 1{a_n} & = \frac 2{a_{n-1}} + \frac 13 & \small \blue{\text{Let }b_k = \frac 1{a_k}} \\ b_n & = 2b_{n-1} + \frac 13 \\ b_0 & = \frac 1{a_0} = \frac 13 = \frac {2^1-1}3 \\ b_1 & = \frac 23 + \frac 13 = 1 = \frac {2^2-1}3 \\ b_2 & = 2 + \frac 13 = \frac 73 = \frac {2^3-1}3 \\ \implies b_n & = \frac {2^{n+1}-1}3 & \small \blue{\text{See proof below.}} \end{aligned}

Therefore, n = 0 100 b n = n = 0 100 2 n + 1 1 3 = 2 ( 2 101 1 ) 101 3 = 2 102 103 3 α + β + γ = 102 + 103 + 3 = 208 \displaystyle \sum_{n=0}^{100} b_n = \sum_{n=0}^{100} \frac {2^{n+1}-1}3 = \frac {2(2^{101}-1)-101}3 = \frac {2^{102}-103}3 \implies \alpha + \beta + \gamma = 102+103+ 3 = \boxed {208} .


Proof: We can prove by induction that b n = 2 n + 1 1 3 b_n = \dfrac {2^{n+1}-1}3 is true for n 0 n \ge 0 . The claim is true for n = 0 n=0 as shown above. Assuming the claim is true for n n , then

b n + 1 = 2 b n + 1 3 = 2 × 2 n + 1 1 3 + 1 3 = 2 n + 2 1 3 \begin{aligned} b_{n+1} & = 2b_n + \frac 13 = 2\times \frac {2^{n+1}-1}3 + \frac 13 = \frac {2^{n+2}-1}3 \end{aligned}

The claim is also true for n + 1 n+1 and hence true for all n 0 n \ge 0 .

Sir, can you help me out with this

Adhiraj Dutta - 1 year, 1 month ago

The given recurrance relation yields 1 a i = 1 3 + 2 a i 1 \dfrac{1}{a_i}=\dfrac{1}{3}+\dfrac{2}{a_{i-1}} .

So, S = 1 a 0 + 1 a 1 + . . . + 1 a 100 = S=\dfrac{1}{a_0}+\dfrac{1}{a_1}+...+\dfrac{1}{a_{100}}=

101 3 + 2 ( S 1 a 100 ) \dfrac{101}{3}+2(S-\frac{1}{a_{100}}) . And 1 a 100 = 1 3 + 2 3 + 4 3 + . . . + 2 100 3 = 2 101 1 3 \dfrac{1}{a_{100}}=\dfrac{1}{3}+\dfrac{2}{3}+\dfrac{4}{3}+...+\dfrac{2^{100}}{3}=\dfrac{2^{101}-1}{3}

S = 2 a 100 101 3 = 2 102 103 3 \implies S=\dfrac{2}{a_{100}}-\dfrac{101}{3}=\dfrac{2^{102}-103}{3} . Hence α = 102 , β = 103 , γ = 3 α=102, β=103, \gamma=3 , and α + β + γ = 102 + 103 + 3 = 208 α+β+\gamma=102+103+3=\boxed {208} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...